2018
DOI: 10.1536/ihj.17-713
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Sarcoidosis Mimicking Septal Tumor with Intermittent Complete Atrioventricular Block

Abstract: A 52-year-old woman with intermittent complete atrioventricular (AV) block detected on exercise was admitted to the hospital. Echocardiography revealed lesions on the right ventricular side of the interventricular septum and free wall of the basal inferolateral area. Gadolinium-enhanced cardiovascular magnetic resonance (CMR) imaging revealed the mass and wall thickening at the same locations with late gadolinium enhancement (LGE). Focal uptake at the septal lesion was detected using 67Ga scintigraphy. Focal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…As previously noted, while some authors have argued that the possibility of disease progression should warrant ICD implantation even if the high-grade or complete AV conduction block transiently recovers, this stance appears to be challenged by emerging case report literature [12][13][14][15][16]. Our patient's successful response to steroid therapy, though, should not be entirely surprising given that his patient profile was consistent with known factors associated with potential improvement in response to therapy in CS patients presenting with AVBs [11,12].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…As previously noted, while some authors have argued that the possibility of disease progression should warrant ICD implantation even if the high-grade or complete AV conduction block transiently recovers, this stance appears to be challenged by emerging case report literature [12][13][14][15][16]. Our patient's successful response to steroid therapy, though, should not be entirely surprising given that his patient profile was consistent with known factors associated with potential improvement in response to therapy in CS patients presenting with AVBs [11,12].…”
Section: Discussionmentioning
confidence: 60%
“…As mentioned before, the patient has not received an EPS and remains asymptomatic as well. Further, most cases of AVB recovery on steroid therapy have occurred in patients with normal LV dysfunction like our patient [9,14,15]. Thus, while the initial management strategy included both steroid therapy and ICD implantation, recovery of his transient AVB, as well as the patient's reluctance toward an invasive procedure, led to a shared decision to continue with only steroid therapy so long as the patient had a reliable follow-up with the proper specialists.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, cardiac tumors also need to be differentiated from other rare diseases to improve the accuracy of clinical diagnosis. 9) Angiosarcoma is the most common histologic subtype of primary cardiac malignant tumors among adults, 1,2) and it usually occurs in men aged 65 years, with a male-to-female ratio of around 2-3:1. 4,7) The most vulnerable site is in the right atrium, with 74% of primary cardiac angiosarcomas occurring in the right atrium and often involving adjacent structures.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Sarcoidosis presenting as a single intramyocardial mass mimicking a cardiac tumour is uncommon. 2 On review of previously reported cases, this case appears to be an extremely rare instance of multiple masses mimicking tumours. This case highlights the utility of multimodality imaging and biopsy in the work-up of this unusual presentation.…”
mentioning
confidence: 84%